Approaches to unaccompanied minors following status determination in Ireland - Sarah Groarke; Samantha Arnold (The Economic and Social Research Institute (ESRI), 2018)
In 2017, over 650,000 people lodged an application for international protection in the EU, 31,395 of whom were unaccompanied minors, constituting more than a 30 per cent increase since 2014. The number of unaccompanied minors recorded in Ireland is low compared to other EU Member States. However, consistent with EU and international trends, this number has increased since 2014. In 2017, 175 unaccompanied minors were referred to the Child and Family Agency, Tusla, Social Work Team for Separated Children Seeking Asylum in Dublin, up from 97 in 2014. This study examines the policies and practices on unaccompanied minors following an international protection or immigration status decision in Ireland. Principally, it considers two potential outcomes for unaccompanied minors in Ireland: a positive decision for immigration permission or international protection and subsequent integration in-country, and forced or voluntary return. The situation of unaccompanied minors turning 18 is highlighted in particular throughout the report, which also presents information on implications arising from a lack of status.
Keywords: 330